(untitled) (Journal of the College of Education for Women, 2019)
The research focuses,in the first place, on six fields.The most important one iscurriculum field which includes the revision of the current academic curriculums andsubstitute them with recent ones, beside the rehabilitation of academic labs and factories byproviding them with modern scientific technologies employed in the world. Regarding theeconomical field, it seeks to provide high-level training staffs to serve different social andeconomical sectors through modern effective technological and scientificcurriculums.Whereas the social field assures the concern of different social classes whodeprived from the grace of higher education such as retirees and elderly people and to set-upsome educational and entertaining seminars for them.Media field deals with Arab MediaOrganizations and how they were far enough from the college and its accomplishments on thepretext of colleges’ weakness to present the new. Concerningthe financial field,it mentionsthat countries in Arab World is the only financer for higher education and scientific research,while we find that most of industrial world countries allocate, for higher education, more than3% of the national income,beside the national effort’s contribution of economicalorganizations for the scientific research in making use of it to solve some of their problems orto buy the scientific accomplishment in order to manufacture it.Student’s field handles thephilosophy of quantitative and voluntary acceptance of students without looking at the size ofqualitative requirements from administrative and technical qualifications and without payingattention to the size of Arab Market. This leads to unemployment of graduates all over ArabCountries. The solution for this problem lies in establishing specialized civil and semigovernmentalfirms whichaim to attract graduates according to their specialties and to ensuretheir government officials privileges as conduct by modern industrial countries all over theworld.